2011
DOI: 10.1134/s1070428011090259
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of macrolides containing an azine or hydrazide fragment via successive tishchenko disproportionation and [1 + 1]-condensation

Abstract: Eight potentially useful 15-, 17-, 20-, and 22-25-membered macrolides having an azine or hydrazide fragment were synthesized starting from L-menthol, tetrahydropyran, and 4-methyltetrahydropyran via [1 + 1]-condensation of hydrazine hydrate and some dicarboxylic dihydrazides with 7-oxooctyl 7-oxooctanoate, 3-methyl-7-oxooctyl 3-methyl-7-oxooctanoate, and (3R)-3,7-dimethyl-6-oxooctyl (3R)-3,7-dimethyl-6-oxooctanoate obtained by the Tishchenko reaction from 7-oxo-, 3-methyl-7-oxo, and (3R)-3,7-dimethyl-6-oxoocta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…[1,2] Their [1+1]-condensation with hydrazine hydrate or dihydrazides of malonic, glutaric, adipic, [1,2] azelaic, sebacic, 7-oxabicyclo[2.2.1]heptenoic [3] and tartaric [4,5] acids led to macroheterocycles containing one or two ester groups and azine or dihydrazide fragments. One of the synthesized macrolides 4 showed a significant (at the level of erythromycin) antibacterial activity in vitro and in vivo against the museum and field strains of pathogenic microorganisms (Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa).…”
Section: Synthesis Of Macrolides With Hydrazide Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Their [1+1]-condensation with hydrazine hydrate or dihydrazides of malonic, glutaric, adipic, [1,2] azelaic, sebacic, 7-oxabicyclo[2.2.1]heptenoic [3] and tartaric [4,5] acids led to macroheterocycles containing one or two ester groups and azine or dihydrazide fragments. One of the synthesized macrolides 4 showed a significant (at the level of erythromycin) antibacterial activity in vitro and in vivo against the museum and field strains of pathogenic microorganisms (Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa).…”
Section: Synthesis Of Macrolides With Hydrazide Fragmentsmentioning
confidence: 99%
“…The 13 C NMR spectra of the reaction products 6 and 7 did not show any signals of carbonyl carbon atoms of initial compounds 2 and 3 (208.86 ppm and 208.99 ppm in 6 and 208.66 ppm in 7). Furthermore, 1 H NMR spectra of the macrocycles 6 and 7 did not show resonances of the hydrazine group (NH 2 NH) (~4.63 ppm). These facts indicated that the products were not the linear substitution products.…”
mentioning
confidence: 99%
“…We recently reported [5] on the synthesis of eight potentially useful 15-, 17-, 20-, and 22-25-membered macrocycles having an azine or hydrazide fragment starting from L-menthol (I), tetrahydropyran (II), and 4-methyltetrahydropyran (III) via consecutive Tishchenko reaction and [1 + 1]-condensation.…”
mentioning
confidence: 99%
“…Macrolides with nitrogen-containing (azine or hydrazide) fragments are commonly prepared by the Tishchenko disproportionation of ketoaldehydes to α,ω-diketo esters or [2 + 1]-condensation of hydroxy esters with α,ω-dicarboxylic acid dichlorides and subsequent macrocyclization by the action of an equimolar amount of hydrazine hydrate or α,ω-dicarboxylic acid hydrazides [1][2][3][4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…Herein we report the transformations of compounds 2 and 3 in reactions with bicyclo[2.2.1]heptane-2-endo,3-endo-dicarbohydrazide (5) and its 5-endo,6-endo-and 5-endo,6-exodihydroxy derivatives 6a and 6b which were prepared DOI: 10.1134/S1070428015060020 Scheme 1. (4). Dihydrazide 5 was synthesized by treatment of 4 with excess hydrazine hydrate in ethanol at 25°C, and compounds 6a and 6b were obtained in a similar way from the corresponding dihydroxy derivatives 7a and 7b.…”
mentioning
confidence: 99%